2017
DOI: 10.1371/journal.pone.0185296
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcification and cardiac function according to residual renal function in patients on hemodialysis with urination

Abstract: BackgroundVascular calcification is common and may affect cardiac function in patients with end-stage renal disease (ESRD). However, little is known about the effect of residual renal function on vascular calcification and cardiac function in patients on hemodialysis.MethodsThis study was conducted between January 2014 and January 2017. One hundred six patients with residual renal function on maintenance hemodialysis for 3 months were recruited. We used residual renal urea clearance (KRU) to measure residual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…Although there is a relationship between IDWG and BP increase in the LII, this relationship is not linear 34 . Thus, we did not find a difference between the two groups regarding mean BP, proportion of patients with adequate BP levels at the end of the interval, and amount of antihypertensive drugs used, findings similar to those reported in the literature 12,30,32 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although there is a relationship between IDWG and BP increase in the LII, this relationship is not linear 34 . Thus, we did not find a difference between the two groups regarding mean BP, proportion of patients with adequate BP levels at the end of the interval, and amount of antihypertensive drugs used, findings similar to those reported in the literature 12,30,32 .…”
Section: Discussionsupporting
confidence: 90%
“…The results in the literature are controversial in this regard. Indeed, Shin et al 32 , when comparing patients with urea clearance higher and lower than 0.9 mL/min in three Korean HD units, also found no difference between the groups for serum calcium levels (8.7 x 8.6 mg/dL, p = 0.92). On the other hand, Wang et al 30 performed a single-center study with 134 Chinese patients who found lower calcium values in the RRF group (9.1 x 9.8 mg/dL; p < 0.001).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For this prospective observational study, we enrolled patients undergoing haemodialysis at three dialysis clinics (Kangdong Sacred Heart Hospital, Kangnam Sacred Heart Hospital, and Chuncheon Sacred Heart Hospital) between January 2014 and February 2015. Of note, based on these patients' clinical data, we previously showed the associations between vascular calcification and various clinical characteristics 28,29 . All patients regularly underwent vascular access monitoring and surveillance according to the KDOQI guidelines.…”
Section: Discussionmentioning
confidence: 75%
“…34 One study reports a progressive increase of arterial stiffness as a predictor of mortality and cardiovascular events among patients with end-stage kidney failure, regardless of anemia, nutrition levels and hemoglobin variability. 35 Patients with CKD may experience arterial stiffness due to decreased arterial compliance and glomerular filtration. 34 When comparing clinical variables with arterial stiffness, systolic blood pressure (SBP) was found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%